A Study of Al 7075 Alloy’s Strengthening and Wear Resistance with SiC and Graphite Hybrid Reinforcement - Murugesan, Ramesh; Dhawood, Samsudeensadham Sheik (Archives of Metallurgy and Materials, 2026)
The hybrid reinforcement of SiC and graphite was used to study the mechanical and tribological properties of Al 7075 alloy. Five weight percent Gr and ten weight percent SiC were added to Al 7075, which has a very high strength-to-weight ratio. The testing included hardness, wear resistance, tensile strength, and coefficient of friction. The hybrid composite performed better than the unreinforced alloy in all respects. Hardness increased from 130–135 BHN to 170–180 BHN, and tensile strength increased from 510–540 MPa to 600–630 MPa. The wear rate decreased from 8.5 × 10⁻⁴ to 3.5 × 10⁻⁴ mm³/N·m, and coefficient of friction reduced to 0.30–0.32. SEM studies revealed good distribution of reinforcement with less porosity. The main advantage of this hybrid composite is SiC bearing the load, whereas graphite provides good lubrication.